Serological, Morphological and Molecular Diagnosis of Mycobacterium bovis in Cattle at Sulaimani Province of Iraq - Rashid, Shorsh Gharib; Sulaiman, Rizgar Raheem; Saeed, Nahla Mohammed (Sulaimani Journal for Pure and Applied Sciences, 2023)
Background: Mycobacterium bovis (M. bovis) causes bovine tuberculosis (BTB), is an endemic disease in cattle and poses a high risk of spreading to humans. Objective: This study aimed to determine M. bovis in cattle and assess the similarities between cattle and humans through molecular methods and histopathological examinations. Methodology: Randomly, blood samples from 411 healthy appearance cows (1% of the target population) in five districts in Sulaimani province, Iraq, were collected from January to March 2022. Sera were obtained immediately and used for ELISA test to determine M. bovis. Additionally, the disease prevalence was confirmed by gross lesions at the slaughterhouse and histopathological examination of collected lymph nodes. Moreover, a PCR assay was used to detect M. bovis in suspected cow samples and previously diagnosed human samples. Gene sequencing and phylogenetic tree analysis were also done to determine the molecular differences between animal and human M. bovis. Results: Using an ELISA test, 46 (11.11%) of 414 samples were positive, while 368 (88.89%) were negative without significant differences between the districts (p>0.05). According to postmortem lesions at the slaughterhouse, only three cows were infected with TB, and typical gross lesions were calcified necrotic and multiple well-demarcated granulomas. The molecular test using two primers (CSB2 and oxyR gene) revealed that M. bovis was found in animal and human extra-pulmonary lymph nodes with no molecular change. Conclusion: Healthy cows harbored M. bovis, the causative agent of a contagious disease that spreads and causes a persistent health problem in humans.
Keywords: Tuberculosis; contagious disease; extra pulmonary lesions; molecular diagnosis